The involvement of 4‐1BB/4‐1BBL signaling in glial cell‐mediated hypothalamic inflammation in obesity. Issue 5 (19th April 2018) - Kim, Jiye; Kwon, Yoon‐Hee; Kim, Chu‐Sook; Tu, Thai H.; Kim, Byung‐Sam; Joe, Yeonsoo; Chung, Hun T.; Goto, Tsuyoshi; Kawada, Teruo; Park, Taesun; Choi, Myung‐Sook; Kim, Min‐Seon; et al.
Abstract : Obesity‐induced inflammation occurs not only in peripheral tissues but also in areas of the central nervous system. Glial cells such as astrocytes and microglia play crucial roles in obesity‐related hypothalamic inflammation, leading to the derangement of energy metabolism and neurodegenerative pathologies. Here, we show that the interaction of 4‐1BB/4‐1BBL between lipid‐laden astrocytes/microglia promotes hypothalamic inflammation in obesity. Stimulation of 4‐1BB, a member of the TNF receptor superfamily, and/or its ligand 4‐1BBL on astrocytes and/or microglia with a specific agonist resulted in activation of the inflammatory signaling pathway and enhanced production of inflammatory mediators. Contact coculture of lipid‐laden astrocytes and microglia increased the production of inflammatory mediators, and blockade of the 4‐1BB/4‐1BBL interaction reduced the inflammatory response. Moreover, deficiency of 4‐1BB reduced hypothalamic inflammation in obese mice fed an high‐fat diet. These findings suggest that 4‐1BBL/4‐1BB signaling enhances the glial cell‐mediated inflammatory cross talk and participates in obesity‐induced hypothalamic inflammation. Abstract : Glial cells such as astrocytes and microglia play crucial roles in hypothalamic inflammation, which is closely associated with metabolic derangements and neurotoxic pathologies. Here, we show that 4‐1BB/4‐1BBL signaling enhances the glial cell‐mediated inflammatory cross talk and participates in obesity‐induced hypothalamic inflammation.